Strategies To Improve Nurse Compliance With Ventilator-Associated Pneumonia Bundle Implementation In Intensive Care Units: A Scoping Review - Permana, Septa; Kosasih, Cecep Eli; Mirwanti, Ristina (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2025)
Background: Ventilator-associated pneumonia (VAP) remains a leading cause of morbidity and mortality among patients in intensive care units (ICUs). Nurses play a central role in preventing VAP through consistent implementation of evidence-based prevention bundles. Although VAP bundles are widely recommended, suboptimal adherence among nurses continues to contribute to high VAP incidence rates, highlighting the need for strategies that improve compliance. Objective: This scoping review aimed to identify and synthesize interventions designed to enhance nurse compliance with VAP bundle implementation in ICU settings. Methods: A scoping review was conducted using the Population–Concept–Context (PCC) framework, focusing on nurses, interventions to improve VAP bundle compliance, and ICU settings. Electronic databases—including PubMed, Cochrane Library, ProQuest, EBSCOhost, ScienceDirect, ClinicalKey, SAGE Journals, and Google Scholar—were searched for full-text articles published in English between 2016 and 2021. Study selection followed the PRISMA framework. Data were extracted, analyzed, and synthesized narratively. Results: From 945 identified records, eight studies met the inclusion criteria. The reviewed literature identified educational and training programs, experiential learning strategies, interprofessional collaboration, and real-time compliance monitoring dashboards as effective interventions to improve nurse adherence to VAP bundles. Conclusion: Multifaceted interventions, particularly continuous education supported by supervision and monitoring, are effective in enhancing nurse compliance with VAP bundle implementation. Sustained organizational support is essential to improve adherence and reduce VAP incidence in ICU settings.